Prevalence and significance of a canine bocavirus-2 outbreak in a cohort of military dogs in Austria - Doulidis, P. G.; Reisner, R.; Auer, A.; Dimmel, Katharina; Lammer, Thomas; Künzel, F. (Frontiers in Veterinary Science, 2024)
IntroductionBocaviruses are single-stranded DNA viruses from the Parvoviridae family, which have been minimally discussed in veterinary literature and are considered potentially pathogenic. Due to the recurring illness among young dogs in a closed cohort of military dogs in Austria, we assessed the prevalence, possible disease manifestation and outcome of CBoV-2 infection in this cohort.Materials and methodsThis led to a comprehensive study that not only analyzed past cases but also performed prospective screening PCR tests to identify CBoV-2 positive dogs within this specific dog population. Pharyngeal and rectal swabs were taken. In addition, a control group (n = 20) of clinically healthy client-owned dogs was sampled. A total of 190 samples were taken and tested for the presence of CBoV-2 specific nucleic acid using screening PCR. In addition to the primers used for routine diagnostics, two other primer pairs were used to verify questionable results. The retrospective part of the study includes a total of 13 military dogs that had previously shown suspected clinical signs.ResultsAt the time of the first examination within the prospective part of the study, CBoV-2 was detected in 31% (12/39) of the dogs. During the second examination, 2% (1/47) tested positive, while all PCR testing in the control group (n = 20) was negative in all cases. The retrospective evaluation of the 13 cases revealed a total of six animals tested positive for CBoV-2 via screening PCR. All puppies suffered from skin lesions (papules, vesicles, or pustules). Other clinical signs included diarrhea (83%), vomiting (77%), respiratory (15%), and neurological (8%) signs.DiscussionAccording to the study there are certain indications that CBoV-2 shares similarities with CPV-2 infection but also exhibits critical differences, making their differentiation essential for patient management, outcomes, and prevention strategies.